Antibacterial Activity of Avicennia alba Leaves and Stem Extracts Against Pathogenic Bacteria (Pseudomonas aeruginosa, Aeromonas salmonicida, Staphylococcus aureus) - Purba, Paedo Yayaki; Yoswaty, Dessy; Nursyirwani, Nursyirwani (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2022)
This research was conducted in November 2020-February 2021 at the Laboratory of Fish Quarantine and Quality Control (BKIPM) Pekanbaru, Riau. The aim of this research was to test the activity of A. alba mangrove leaf extracts and stems in inhibiting the growth of pathogenic bacteria P.aeruginosa, A.salmonicida, and S.aureus. The research method used in this study is the experimental method. The sampling was conducted at the location of Marine Station UNRI Purnama Dumai. The results showed that A. alba leaf extract has the highest inhibitory power at a concentration of 100% with an average of 4.37–5.13 mm. The highest inhibitory power was against S.aureus (5.13 mm) and the lowest inhibition power was found in A. salmonicida (4.37 mm). The lowest inhibition was found at a concentration of 12.5% with an average of 0.45–0.67 mm. The stem extract of A. alba had the highest inhibitory power at a concentration of 100% with an average of 6.17–7.47 mm. The highest inhibition power was against S. aureus 7.47 mm and the lowest inhibition power was found in A.salmonicida (6.17 mm). The lowest inhibitory was at a concentration of 12.5% with an average of 1.52–2.29 mm. Based on the criteria for the strength of antibacterial activity of stem extract A. alba was in the medium category and the leaf extract was in the weak category.